Instruments of legalization of income received by criminal law - Malanchuk, Petro (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the generalization of the main instruments of legalization of proceeds from crime. The main schemes of laundering of proceeds from crime are outlined. Considered virtual money as disadvantages in the global economy. Bitcoin is analyzed as a kind of cryptology. Possible threats associated with use are outlined.